Prognostic Value of Geriatric Nutritional Risk Index in Esophageal Carcinoma: A Systematic Review and Meta-Analysis - Zhou, Jianfeng; Fang, Pinhao; Li, Xiaokun; Luan, Siyuan; Xiao, Xin; Gu, Yinmin; Shang, Qixin; Zhang, Hanlu; Yang, Yushang; Zeng, Xiaoxi; Yuan, Yong (Frontiers in Nutrition, 2022)
Esophageal cancer (EC) is one of the most common cancers worldwide. Malnutrition often leads to poor prognosis of patients with EC. Geriatric nutritional index (GNRI) was reported as an objective nutrition-related risk index. We intend to comprehensively review evidence of GNRI in EC prognosis predicting. To explore the influence of GNRI on the long-term survival outcome of EC patients, a meta-analysis was needed. We searched the web of science, Medline, Embase, and the Cochrane Library databases. The association between prognosis of patients with EC and GNRI was evaluated by pooling hazard ratios (HRs) and their corresponding 95% confidence intervals (CIs). Fixed model or random model method was chosen according to the heterogeneity among the studies. Totally, 11 studies with 1361 patients met the inclusion criteria were eventually included in our meta-analysis. Comparing lower level GNRI group and the higher level GNRI group, the pooled results showed that lower GNRI had a negative impact on overall survival (OS) (HR 1.75, 95% CI: 1.45-2.10, P<0.01), cancer specific survival (CSS) (HR 1.77, 95% CI: 1.19-2.62, P<0.01), indicating that lower GNRI significantly predicted poor OS. In conclusion, lower GNRI could predict the poor prognosis of EC patients. Meanwhile, more well-designed RCTs are needed to confirm the findings.